Pengaruh Peran Kepala Sekolah Terhadap Peningkatan Kualitas Kinerja Mengajar Guru di SMK Negeri 1 Kota Gorontalo - Febriyanti Mardjun; Muhammad Amir Arham; Radia Hafid; Usman Moonti; Sudirman Sudirman (State University of Gorontalo, 2023)
The objective of this research was to determine the influence of the role of the school principal on improving the quality of teacher performance at SMK Negeri 1 Kota Gorontalo. This research employed a quantitative approach with a quantitative research method. The data used were primary data obtained by distributing questionnaires to teachers and education staff at SMK Negeri 1 Kota Gorontalo, which amounted to 35 respondents. In the meantime, the data analysis technique used was simple linear regression. The research finding revealed that the role of the school principal (X) at SMK Negeri 1 Kota Gorontalo. This result signified that the role of the school principal could improve teacher Performance at SMK Negeri 1 Kota Gorontalo.